CHRISTIAN DALITS: A HISTORICAL PERSPECTIVE: . - Massey, James (Journal of Dharma, 1991)
’Dalits’ is the plural of dalit which in Sanskrit language is both noun and adjective. As a noun ’dalit’ can be used for all three genders’ "masculine, feminine and neuter. It is derived from the root ’dal’ means to crack, open, split etc. When used as a noun or an adjective, it means burst, split, broken or torn asunder, trodden down, scattered, destroyed etc.’